Covalent Organic Frameworks for Catalysis. Issue 3 (June 2020) - Yusran, Yusran; Li, Hui; Guan, Xinyu; Fang, Qianrong; Qiu, Shilun
Highlights: We comprehensively elaborate the designed synthesis of COF-based catalysts and their applications in the field of chemical catalysis, photocatalysis and electrocatalysis. We further indicate the significant advantages of COFs in the catalytic studies, in reference to traditional catalysts. The challenges and prospects for developing COF-based catalysts are also discussed. ABSTRACT: Covalent organic frameworks (COFs) are an emerging class of crystalline porous polymers with pre-designed structures and tailored compositions. The adjustable porosities, high thermal and chemical stabilities, tunable functionalities and flexibility in installing catalytic active sites translate COFs into highly promising catalytic materials. In this review, we comprehensively elaborate the designed synthesis of COF-based catalysts and their applications in the field of chemical catalysis, photocatalysis and electrocatalysis. We further indicate the significant advantages of COFs in the catalytic studies, in reference to traditional catalysts. Finally, the challenges and prospects for developing COF-based catalysts are also discussed. Graphical abstract: Image, graphical abstract